Understanding the early career self-initiated expatriation: A review and directions for future research - Li, Xueyan; Primecz, Henriett; Paget, Anna Laura (Vezetéstudomány / Budapest Management Review, 2023)
While the literature on self-initiated expatriation (SIE) is well-established in management, no systematic investigation has yet been conducted to explore the specificities of early career expatriation. This review article aims to identify and analyse publications that uniquely focus on self-initiated expatriates, who decide to start their career abroad, either with little or no prior work experience. After identifying relevant publications in this specific research field, the authors discuss the personal career motivations and behaviours of early career self-initiated expatriates and the relevance of this phenomenon for the global workforce. The contributions of this article are twofold. First, they integrate the relevant research findings from recent decades on early career self-initiated expatriates. Second, they provide information about managing early career SIEs and propose a future research agenda to address the knowledge gap identified in this review and apply the findings to practice.